1996
DOI: 10.1016/s0009-9236(96)90150-2
|View full text |Cite
|
Sign up to set email alerts
|

Concentration-related pharmacodynamic effects of thioridazine and its metabolites in humans

Abstract: These data suggest that thioridazine has dose-related effects on ventricular repolarization and that the parent drug causes an important proportion of these effects, although its metabolites may also contribute.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(56 citation statements)
references
References 33 publications
2
53
1
Order By: Relevance
“…*P b 0.05, **P b 0.01, and ***P b 0.0001. QTc prolongation, and Torsades de Pointes (Harrigan et al, 2004;Hartigan-Go et al, 1996;Thomas, 1994;Kelly, 1963), the structural toxicity shown is indicative of more direct damage on cardiomyocytes, which has been shown in previous nonclinical studies (Hull and Lockwood, 1986). Amiodarone, an antiarrhythmic, also showed significant structural effects, inducing lipids at 2 × its Cmax and increasing ROS and cell death at 17× its Cmax.…”
Section: Discussionmentioning
confidence: 74%
“…*P b 0.05, **P b 0.01, and ***P b 0.0001. QTc prolongation, and Torsades de Pointes (Harrigan et al, 2004;Hartigan-Go et al, 1996;Thomas, 1994;Kelly, 1963), the structural toxicity shown is indicative of more direct damage on cardiomyocytes, which has been shown in previous nonclinical studies (Hull and Lockwood, 1986). Amiodarone, an antiarrhythmic, also showed significant structural effects, inducing lipids at 2 × its Cmax and increasing ROS and cell death at 17× its Cmax.…”
Section: Discussionmentioning
confidence: 74%
“…Phenothiazine drugs are largely metabolized by CYP2D6 (Llerena et al, 2000) with subsequent phase II metabolism. The major phase II metabolites commonly reported are sulfate conjugates (Hartigan-Go et al, 1996), but glucuronide conjugates have also been reported as the major urinary metabolite of phenothiazine drugs (Pieniaszek et al, 1999). The precise metabolic profile for trifluoperazine is unknown, but the contribution of UGT1A4 may not be the deciding factor in total hepatic clearance.…”
Section: Miyagi and Colliermentioning
confidence: 99%
“…In the second study, Hartigan-Go et al 19 did a randomised, double-blind, three-period crossover study involving 9 healthy male subjects. They reported a dose-related prolongation of the to abnormal levels in almost one-quarter of subjects and to dangerous levels in 2 patients.…”
Section: Resultsmentioning
confidence: 99%